2023
DOI: 10.7759/cureus.33989
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients With Parkinson’s Disease: A Cross-Sectional Study

Abstract: Patients with Parkinson's disease (PD) suffer from a range of physical, psychological, and social problems. The disease affects the quality of life (QOL) of the affected person. Several factors contribute to QOL, and these factors should be examined to develop appropriate strategies. This study aimed to determine the factors related to QOL in patients with PD. A cross-sectional, descriptive study was conducted using a tool with strong validity and reliability (39-Item Parkinson's Disease Questionnaire (PDQ-39)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…The analysis showed a mean difference of -12.13 (95% CI [-15.43, -8.83], p < 0.00001). A study conducted in Saudi Arabia revealed that several domain-based variables influenced the quality of life (QOL) of individuals with PD, including frequent hospitalizations, education level, and marriage status (Al-Khammash et al, 2023). A meta-analysis study found that PD patients had significantly poorer quality of life (QOL) compared to healthy controls, highlighting the need for effective measures to improve QOL in this patient population (Zhao et al, 2021).…”
Section: Quality Of Lifementioning
confidence: 99%
“…The analysis showed a mean difference of -12.13 (95% CI [-15.43, -8.83], p < 0.00001). A study conducted in Saudi Arabia revealed that several domain-based variables influenced the quality of life (QOL) of individuals with PD, including frequent hospitalizations, education level, and marriage status (Al-Khammash et al, 2023). A meta-analysis study found that PD patients had significantly poorer quality of life (QOL) compared to healthy controls, highlighting the need for effective measures to improve QOL in this patient population (Zhao et al, 2021).…”
Section: Quality Of Lifementioning
confidence: 99%
“…Worsening motor functions, advanced stage of disease, and higher prevalence of falls may deteriorate the psychological aspects of QOL. There is a negative effect of depression on the QOL of patients with PD and depression is the most important determinant of QOL [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Reported non-motor symptoms include autonomic and gastrointestinal problems, olfactory and sleep deficits, anxious and depressive symptoms, and cognitive impairment, among others [3,4]. Starting with mild symptoms, the disease gradually progresses to a level where daily activities and quality of life are negatively impacted [5].…”
Section: Introductionmentioning
confidence: 99%